(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The nature and size of the productive structure of economies represent fundamental determinants of sustainable economic growth and their ability to adapt to the economic shocks faced by these economies. Therefore, the study aims to measure the impact of the nature of the productive structure, represented by the economic complexity index and its determinants (knowledge and innovation), on sustainable economic growth (represented by the GDP per capita by PPP) in Arab countries. Also, it aims to measure the extent to which these countries can absorb those shocks through their ability to sustain their export revenues from highly complex goods. The results show an insignificant impact of economic complexity on GDP per capita by PPP. This is because developing countries (including Arab countries) face fluctuations in their export revenues of low-complexity exported products (low added value). This requires economic policymakers to formulate effective strategies aimed to enhance innovation and cognitive ability and creating a diversified economy with competitiveness and sustainable economic growth.